Aortic stiffness is increased in polymyalgia rheumatica and improves after steroid treatment. Issue 7 (20th January 2012) - Schillaci, Giuseppe; Bartoloni, Elena; Pucci, Giacomo; Pirro, Matteo; Settimi, Laura; Alunno, Alessia; Gerli, Roberto; Mannarino, Elmo
Abstract : Background: Inflammatory rheumatic diseases have been associated with increased cardiovascular risk and arterial stiffness. Polymyalgia rheumatica (PMR), a disease which affects primarily older people, is characterised by a systemic inflammatory response but little is known about aortic involvement in PMR. A study was undertaken to investigate whether aortic stiffness is increased in PMR and whether it improves after steroid treatment. Methods: Thirty-nine patients with PMR (age 72±8 years, 44% men, blood pressure (BP) 134/75±16/9 mm Hg) and 39 age-, sex- and BP-matched control subjects underwent aortic pulse wave velocity (PWV) determination. Aortic augmentation as a measure of the impact of the reflection wave on central haemodynamics was also measured and corrected for heart rate. Twenty-nine of the patients were re-examined after 4 weeks of treatment with prednisone at a dose of 15 mg/day. Results: Aortic PWV was higher in patients with PMR than in control subjects (12.4±4 vs 10.2±2 m/s, p<0.01). Treatment was followed by a reduction in heart rate (from 78±12 to 70±10 beats/min, p<0.001) and no significant change in BP. Aortic PWV decreased after prednisone treatment (from 11.8±3 to 10.5±3 m/s, p=0.015), and the difference was independent of BP and heart rate changes. The change in aortic PWV had a direct correlation with percentage change in plasma C reactive protein (r=0.40, p=0.037). Treatment was also associated with a significant reduction in aortic augmentation index (from 34±7% to 29±8%, p=0.012). Conclusions: Polymyalgia rheumatica is associated with increased aortic stiffness which may improve upon reduction of systemic inflammation induced by treatment with glucocorticoids.